ENUMERATION OF MICROBIAL POPULATION FROM RICE FIELDS AND THEIR DEHYDROGENASE ACTIVITIES IN TWO CROPPING SEASONS IN EASTERN INDIA - MAHASWETA DAS; PRAKASH KUMAR SARANGI; NGANGKHAM JOYKUMAR SINGH (The Bioscan, 2015)
A field experiment was carried out to study the different microbial population in rice field with respect to their dehydrogenase(respiratory enzyme)activity during Kharif(July- Oct) (wet) and rabi(Jan-may) (dry)in the year 2013. The rice cultivar Lalat was taken for cultivation. Different micro flora was observed under both the cropping system. The population like heterotrophs, anaerobic population, fungal population and actinobateria population was isolated under different stages of crop. During Kharif seasons the heterotrophic bacterial population was significantly higher under panicle initiation stage of rice crop (cvlalat). The fungal population was not significant amongthe different stages of rice crop.. Dehydrogenase activity was significantly higher under panicle initiation stage of both rabi(dry)and kharif(wet)rice crop. Dehydrogenase activity was 20% more under PI stage than maximum tillering stage in kharif seasons. In kharifseasons the anaerobic bacteria population was significantly higher as compare with rabiseasons. Soil dehydrogenase enzymes are one of the main components of soil enzymatic activities participating in and assuring the correct sequence of all the biochemical routes in soil biogeochemical cycles thereby regulating the microbial diversity.Environmental sustainability point of view, different micro flora present in rhizospheric soil under rice-rice cropping system in tropical low land soil could be adopted to maintain soil health, increased yield rate and increased carbon pools and dehydrogenase enzyme which is good indicator of fertile soil.